Method for manufacturing laminate structure, method for manufacturing cable, and method for manufacturing tube
A laminated structure with silicone rubber and UV-blocking particles enhances UV-C light resistance and slipperiness in medical device cables, addressing deterioration issues.
Patent Information
- Application Number
- JP2024162448
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-02-09
AI Technical Summary
Silicone rubber sheaths used in medical device cables deteriorate under UV-C light irradiation, leading to cracks when stressed, such as by bending, due to insufficient resistance.
A laminated structure with a silicone rubber base material and a second layer containing first fine particles for surface unevenness and second fine particles for UV-C light blocking, enhancing resistance and slipperiness.
The laminated structure provides excellent resistance to UV-C light and improved slipperiness, preventing cable deterioration and easy handling.
Smart Images

Figure 2024175109000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a laminated structure, a method for manufacturing a cable, and a method for manufacturing a tube. [Background technology]
[0002] Conventionally, medical device cables have been known that are made of silicone rubber containing fine particles and have a coating that covers the sheath (see Patent Document 1). Compared to polyvinyl chloride (PVC), which has traditionally been used commonly as a sheath material, silicone rubber has the advantage that it hardly discolors over time, but its surface tends to be less slippery.
[0003] The coating of the cable described in Patent Document 1 is made of silicone rubber containing fine particles, and thus has irregularities on its surface resulting from the fine particles. These irregularities can reduce the contact area when the coating comes into contact with another member, and can increase the slipperiness of the coating surface, i.e., the slipperiness of the cable. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6723489 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, sterilization by UV-C light irradiation has been attracting attention as a simple, inexpensive, and reliable method for sterilizing cables for medical equipment, but the cable's resistance to UV-C light is an issue when sterilizing by UV-C light irradiation. It has been confirmed that even cables with a silicone rubber sheath deteriorate when repeatedly irradiated with UV-C light, and that cracks appear in the sheath when the cable is subjected to stress, such as bending the cable.
[0006] The object of the present invention is to provide a method for manufacturing a laminated structure having a silicone rubber base material and having excellent resistance to UV-C light, as well as a method for manufacturing a cable and a tube having an insulator made of the laminated structure. [Means for solving the problem]
[0007] In order to solve the above-mentioned problems, the present invention provides a method for manufacturing a laminated structure comprising a first layer serving as a base material, and a second layer formed from a rubber composition containing a rubber component, first microparticles for imparting unevenness to the surface, and second microparticles for blocking UV-C light, and laminated on the first layer, the method comprising the steps of: preparing the first layer; applying a liquid rubber composition containing the first microparticles and the second microparticles onto the first layer to form a coating film; and curing the coating film to form the second layer.
[0008] Further, in order to solve the above-mentioned problems, the present invention provides a method for producing a cable or a method for producing a tube having an insulation body made of the above-mentioned laminate structure. Effect of the Invention
[0009] According to the present invention, it is possible to provide a method for manufacturing a laminated structure having a silicone rubber base material and having excellent resistance to UV-C light, as well as a method for manufacturing a cable and a method for manufacturing a tube having an insulator made of the laminated structure. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a vertical sectional view of a laminated structure according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a plan view illustrating a schematic configuration of an ultrasonic probe cable according to a second embodiment of the present invention. [Diagram 3]Fig. 3(a) is a cross-sectional view in the radial direction of the ultrasonic probe cable, and Fig. 3(b) is a cross-sectional view in the radial direction of the ultrasonic probe cable cut along the cutting line AA shown in Fig. 2. [Figure 4] 4(a) to (c) are radial cross-sectional views of a medical tube according to a second embodiment of the present invention. [Diagram 5] Fig. 5(a) is a graph showing the results of the tensile test of sample A1, and Fig. 5(b) is a graph showing the results of the tensile test of sample A2. [Figure 6] Fig. 6(a) is a graph showing the results of the tensile test of sample A3, and Fig. 6(b) is a graph showing the results of the tensile test of sample A4. [Figure 7] Fig. 7(a) is a graph showing the relationship between the UV-C light irradiation time and the stress at break of the substrate for samples A1 to A4, and Fig. 7(b) is a graph showing the relationship between the UV-C light irradiation time and the elongation at break of the substrate for samples A1 to A4. [Figure 8] FIG. 8 is a graph showing the Raman scattering spectrum measured at a certain point on sample B1. [Figure 9] Fig. 9(a) is a mapping image of sample B1 obtained by mapping analysis, and Fig. 9(b) is a binarized analysis image obtained by binarizing the mapping image of Fig. 9(a). [Figure 10] Fig. 10(a) is a mapping image of sample B2 obtained by mapping analysis, and Fig. 10(b) is a binarized analysis image obtained by binarizing the mapping image of Fig. 10(a). [Figure 11] Fig. 11(a) is a mapping image of sample B3 obtained by mapping analysis, and Fig. 11(b) is a binarized analysis image obtained by binarizing the mapping image of Fig. 11(a). [Figure 12] Fig. 12(a) is a mapping image of sample B4 obtained by mapping analysis, and Fig. 12(b) is a binarized analysis image obtained by binarizing the mapping image of Fig. 12(a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First Embodiment (Structure of laminated structure) 1 is a vertical cross-sectional view of a laminated structure 1 according to a first embodiment of the present invention. The laminated structure 1 includes a first layer 10 having a silicone rubber base material, and a second layer 11 laminated on the first layer 10, the second layer 11 having a silicone rubber base material 111 and including first microparticles 112 for imparting unevenness to the surface and second microparticles 113 for blocking UV-C light by absorbing and / or scattering.
[0012] The first particles 112 are made of a material containing Si, such as silicone resin or silica, which has higher resistance to UV-C light than silicone rubber. The average particle size of the second particles 113 is preferably smaller than that of the first particles 112. For example, the average particle size of the second particles 113 is preferably 1 / 2 or less, more preferably 1 / 5 or less, of the average particle size of the first particles 112. This allows the second particles 113 to be segregated around the first particles 112, and the second particles 113 to be selectively arranged in the region in the in-plane direction of the second layer 11 where the first particles 112 are not present. Here, the UV-C light is ultraviolet light in a wavelength range of 200 to 280 nm.
[0013] Silicone rubber, which is the base material of the first layer 10 and the second layer 11, is a type of silicone resin. Silicone rubber has higher resistance to ultraviolet rays (UV-A light and UV-B light) than polyvinyl chloride, which has been commonly used as a material for cables and tubes used in medical applications.
[0014] Furthermore, by adding first microparticles 112, which are microparticles containing Si, such as silicone resin microparticles or silica (silicon oxide) microparticles, to silicone rubber to form irregularities on the surface, it is possible to suppress the stickiness (tack) of the surface and improve the smoothness (slidability). Therefore, by laminating a second layer 11 made of silicone rubber to which the first microparticles 112 have been added on a first layer 10 made of silicone rubber not containing the first microparticles 112 to cover the surface, it is possible to suppress the stickiness of the silicone rubber surface and improve the smoothness.
[0015] On the other hand, silicone rubber that does not contain the first microparticles 112 needs to have a certain degree of thickness so as to have the performance as a base (for example, the function of protecting or containing other items) compared to silicone rubber that contains the first microparticles 112. For this reason, when the laminated structure 1 is used as an insulator for a cable or a tube, it is preferable to form the first layer 10 by extrusion or the like, which has excellent productivity, and then laminate the second layer 11 on top of this by a method such as coating.
[0016] The laminated structure 1 can take various forms depending on its application. For example, it is molded into a tubular shape when used as an insulator for cables or tubes, and it is molded into a sheet shape when used as a highly UV-resistant sheet for a thermostatic house or an UV-shielding sheet (UV-shielding curtain) for blocking UV rays leaking from a sterilization chamber or the like.
[0017] (Second layer configuration) The second layer 11 has an uneven surface because it contains the first fine particles 112. This reduces the contact area when the second layer 11 comes into contact with an object, and increases the slipperiness, compared to when the surface is flat.
[0018] For example, an addition reaction type silicone rubber coating agent or a condensation reaction type silicone rubber coating agent can be used as the silicone rubber which is the base material 111 of the second layer 11. In particular, it is preferable to use an addition reaction type silicone rubber coating agent from the viewpoints of adhesion to the first layer 10 which has silicone rubber as its base material and abrasion resistance.
[0019] In order to obtain good slipperiness and a predetermined wiping resistance on the surface of the laminated structure 1 by the second layer 11, the thickness of the second layer 11 is preferably 3 μm or more. The second layer 11 may be laminated on both sides of the first layer 10. The upper limit of the thickness of the second layer 11 is not particularly limited, but is preferably 100 μm or less from the viewpoints of productivity, high flexibility, and high bendability.
[0020] The first fine particles 112 are, for example, silicone resin fine particles, silica fine particles, or a mixture of these two. The first fine particles 112 preferably have a higher hardness (for example, a hardness of about 1.1 times or more in Shore (Durometer A) hardness) than the base material 111 made of silicone rubber.
[0021] Silicone resins, which have fewer reactive groups (e.g., methyl groups) than silicone rubber, are harder than silicone rubber, and silica, which has no reactive groups, is even harder. In terms of mass, silica has the largest mass, followed by silicone resin and silicone rubber, the smallest.
[0022] From the viewpoint of suppressing deformation of the surface irregularities when the second layer 11 comes into contact with a contacting object, silica, which has high hardness, is the most preferable material for the first fine particles 112, followed by silicone resin. This is because the higher the hardness of the first fine particles 112, the more the deformation of the surface irregularities of the second layer 11 can be suppressed when a pressing pressure is applied to the surface of the second layer 11 by the contacting object. This makes it possible to suppress an increase in the contact area of the second layer 11 with the contacting object and maintain the slipperiness.
[0023] On the other hand, since silica has a large mass as described above, the first microparticles 112 made of silica tend to settle in the silicone rubber coating agent that serves as the base material during the manufacturing process of the second layer 11, and are more difficult to disperse in the silicone rubber (second layer 11) than the first microparticles 112 made of silicone resin. Therefore, from the viewpoint of improving the uniformity of dispersion in the silicone rubber (second layer 11), it is preferable to use the first microparticles 112 made of silicone resin.
[0024] Therefore, in order to achieve both the maintenance of the slipperiness of the second layer 11 when it comes into contact with a contact object and the uniform dispersion of the first microparticles 112 in the silicone rubber base material, it is preferable to use the first microparticles 112 made of silicone resin.
[0025] The average particle size of the first particles 112 is, for example, 1 μm or more and 10 μm or less. The concentration (mass %) of the first particles 112 in the second layer 11 is, for example, 10 mass % or more and 60 mass % or less. Here, the "average particle size" in this specification refers to one measured by a laser diffraction scattering method.
[0026] As described above, the first microparticles 112 have higher resistance to UV-C light than the silicone rubber that is the material of the base material 111. This is because the bond energy between atoms in the molecular structure of the silicone resin or silica that is the material of the first microparticles 112 is higher than the bond energy between atoms in the molecular structure of silicone rubber.
[0027] For example, the C-H bonds found in large quantities in silicone rubber have a bond energy (approximately 4.27 eV) that is smaller than the energy of UV-C light (approximately 6.2 eV), so the bonds are broken when irradiated with UV-C light. However, the Si-O bonds found in large quantities in silicone resin have a bond energy (approximately 6.52 eV) that is greater than the energy of UV-C light, so the bonds are not broken when irradiated with UV-C light.
[0028] The second particles 113 are made of a material that has the property of blocking UV-C light by absorbing and / or scattering it, such as titanium oxide (TiO2), carbon (C), zinc oxide (ZnO), and iron oxide (Fe2O3). The second particles 113 block UV-C light, so that deterioration of the base material 111 made of silicone rubber due to UV-C light can be suppressed. The titanium oxide used as the material of the second particles 113 may be any of anatase type, rutile type, and brookite type, or may be a mixture of two or more types. Niobium oxide may be added to the titanium oxide to provide stability.
[0029] As described above, the average particle size of the second particles 113 is preferably smaller than that of the first particles 112. By reducing the average particle size of the second particles 113, the second particles 113 can be present in the gap spaces between the first particles 112. By reducing the average particle size of the second particles 113 than that of the first particles 112, the second particles 113 can be segregated around the first particles 112, and the second particles 113 can be selectively arranged in the region in the in-plane direction of the second layer 11 where the first particles 112 are not present. For example, the average particle size of the second particles 113 is set to 1 / 2 or less, more preferably 1 / 5 or less, of the average particle size of the first particles 112, so that the second particles 113 can be more effectively segregated around the first particles 112. The lower limit of the average particle size of the second particles 113 is not particularly limited, but from the viewpoint of availability, the average particle size of the second particles 113 is preferably 10 nm or more. Here, the "average particle size" of the second particles 113 refers to that measured by a laser diffraction scattering method.
[0030] When observing the second layer 11 from the surface, the regions where the first microparticles 112 are not present (regions between the first microparticles 112) are regions where only the silicone rubber matrix 111 is present and have low resistance to UV-C light. The inventors of the present application have found that by selectively arranging the second microparticles 113 in these regions to block UV-C light, it is possible to efficiently improve resistance to UV-C light.
[0031] (First layer configuration) In order to suppress deterioration due to UV-C light transmitted through the second layer 11, the first layer 10 preferably includes second fine particles 102 for absorbing UV-C light, similar to the second layer 11 including the second fine particles 113. In this case, as shown in FIG. 1, the first layer 10 includes a silicone rubber base material 101 and the second fine particles 102 dispersed in the base material 101. Note that, as the material of the base material 101, polyethylene, chlorinated polyethylene, chloroprene rubber, polyvinyl chloride (PVC), polyurethane, etc. can also be used. Among them, silicone rubber and chloroprene rubber are preferable from the viewpoint of chemical resistance and heat resistance. Note that, when the first layer 10 is used as a sheath material, it can be an insulating material to which general compounding agents such as various crosslinking agents, crosslinking catalysts, antiaging agents, plasticizers, lubricants, fillers, flame retardants, stabilizers, colorants, etc. are added. Also, instead of the second fine particles 102 dispersed in the base material 101, an organic ultraviolet absorbing agent may be compounded.
[0032] The material of the second particles 102 may be the same as the material of the second particles 113, for example, titanium oxide or carbon. However, it is preferable that the second particles 102 are uniformly dispersed in the base material 101 so that the resistance of the first layer 10 to UV-C light does not vary from place to place. For this reason, the average particle size of the second particles 102 is not particularly limited, but is preferably, for example, 10 nm or more and 1 μm or less. Here, the "average particle size" of the second particles 102 refers to a value measured by a laser diffraction scattering method.
[0033] Second Embodiment The second embodiment of the present invention is a cable or tube having an insulator made of the laminated structure 1 according to the first embodiment. As an example, a cable used for a medical ultrasound probe cable will be described below.
[0034] In recent years, the use of silicone rubber, which has excellent heat resistance and chemical resistance, as a sheath material for cables used in medical applications has been considered. However, as mentioned above, silicone rubber has the problem of poor slipperiness. Therefore, when silicone rubber is used as a cable sheath material, problems arise in that the cable is easily caught on other components and dust is easily attracted to the surface of the cable.
[0035] In particular, if a cable becomes easily caught on other components, it becomes difficult to handle, for example, in a cable connected to a medical device such as an ultrasound imaging device. This is because, in an ultrasound imaging device, an ultrasound probe connected to a probe cable is moved over the human body during examination, and if the probe cable becomes easily caught on other cables or clothing, the ultrasound probe cannot be moved smoothly. Therefore, it is desirable for cables used for medical purposes to be non-sticky and have a good surface slipperiness (static friction coefficient of 0.5 or less).
[0036] Fig. 2 is a plan view showing a schematic configuration of an ultrasonic probe cable 2 according to a second embodiment of the present invention. In the ultrasonic probe cable 2, as shown in Fig. 2, an ultrasonic probe 32 is attached to one end of a cable 20 via a boot 31 that protects the one end. Meanwhile, a connector 33 that is connected to a main body of an ultrasonic imaging device is attached to the other end of the cable 20.
[0037] 3(a) is a cross-sectional view in the radial direction of the cable 20 of the ultrasonic probe cable 2. Electric wires 21, typically a plurality of coaxial cables, are housed inside the cable 20, and a shield 22, such as a braided shield, is provided to cover the plurality of electric wires 21. A sheath 23 is provided to cover the shield 22. Furthermore, in the cable 20, a coating 24 is formed to cover the periphery of the above-mentioned sheath 23 and to be in close contact with the sheath 23.
[0038] Fig. 3(b) is a radial cross-sectional view of the ultrasonic probe cable 2 cut along the cutting line AA shown in Fig. 2. As shown in Fig. 3(b), the boot 31 is attached to the coating 24 via an adhesive layer 34 so as to cover the coating 24. The adhesive layer 34 is formed of, for example, a silicone adhesive or an epoxy adhesive. The boot 31 may also be formed of, for example, PVC, silicone rubber, chloroprene rubber, or the like, and preferably contains second microparticles 102 for blocking UV-C light and an organic ultraviolet absorbing agent, similar to the first layer 10.
[0039] The sheath 23 and coating 24 of the cable 20 are respectively composed of the first layer 10 and the second layer 11 of the laminated structure 1. That is, in the cable 20, the laminated structure 1 is used as the sheath 23 and coating 24. By using the coating 24 composed of the second layer 11 having excellent slipperiness, it is possible to suppress the ultrasonic probe cable 2 from being caught due to the stickiness of the surface of the sheath 23. The thickness of the coating 24 is, for example, 3 μm or more and 100 μm or less. Note that the second fine particles 102 in the sheath 23 and the first fine particles 112 and the second fine particles 113 in the coating 24 are not shown in the drawings.
[0040] Next, an example of a manufacturing method of the ultrasonic probe cable 2 in this embodiment will be described. First, a plurality of electric wires 21 (for example, 100 or more) are bundled together. Then, a shield 22 is formed so as to cover the bundled electric wires 21.
[0041] Next, the first layer 10 and the second layer 11 of the laminated structure 1 are formed in order to cover the shield 22, and the sheath 23 and the coating 24 are formed. The sheath 23 is formed, for example, by extrusion molding using an extruder. The coating 24 is formed, for example, by a dipping method, a spray coating method, a roll coating method, or the like. In the dipping method, the ultrasonic probe cable 2 formed up to the sheath 23 is pulled up through a liquid coating material to form the coating 24 on the surface of the sheath 23. This dipping method is superior to the spray coating method and the roll coating method in terms of the uniformity of the thickness of the coating 24 formed.
[0042] The liquid coating agent used in the dipping method is liquid silicone rubber containing the first fine particles 112 and the second fine particles 113, and contains a solvent such as n-heptane. By adjusting the content of the first fine particles 112 and the second fine particles 113 contained in this liquid coating agent, the content of the first fine particles 112 and the second fine particles 113 contained in the coating 24 can be controlled.
[0043] Further, as another example of a cable or tube having an insulator made of the laminated structure 1, the structure of a tube (hollow tube) used for medical purposes such as a catheter will be described below.
[0044] Figures 4(a) to (c) are radial cross-sectional views of a medical tube according to a second embodiment of the present invention. Medical tube 40a shown in Figure 4(a) has an outer coating 42 on the outer surface 41a of tube body 41. Medical tube 40b shown in Figure 4(b) has an inner coating 43 on the inner surface 41b of tube body 41. Medical tube 40c shown in Figure 4(c) has outer coating 42 and inner coating 43 on the outer surface 41a and inner surface 41b of tube body 41, respectively.
[0045] As exemplified by medical tubes 40a, 40b, and 40c, the tube according to this embodiment comprises a tube body 41, an outer coating 42 covering the outer surface 41a of the tube body 41, an inner coating 43 covering the inner surface 41b of the tube body 41, or both the outer coating 42 and the inner coating 43. The tube body 41 of the medical tubes 40a, 40b, and 40c is made of a first layer 10 of a laminated structure 1, and the outer coating 42 and the inner coating 43 are made of a second layer 11 of the laminated structure 1.
[0046] The tube according to the present embodiment has excellent lubricity on the inner and outer surfaces, and therefore when an instrument is inserted into the tube and used, such as in a medical tube such as a catheter, the instrument can be smoothly inserted and removed. In addition, the tube according to the present embodiment can be used in tube sets for endoscopic surgical instruments, tube sets for ultrasonic surgical instruments, tubes for blood analyzers, piping in oxygen concentrators, artificial dialysis blood circuits, artificial heart-lung circuits, endotracheal tubes, etc.
[0047] (Effects of the embodiment) According to the laminated structure 1 of the first embodiment, the second layer 11 contains the first fine particles 112, and therefore has excellent surface slipperiness, and also has excellent resistance to UV-C light, since the second fine particles 113 are segregated around the first fine particles 112. Moreover, according to the ultrasonic probe cable 2 and medical tubes 40a, 40b, 40c of the second embodiment, the laminated structure 1 is used as an insulator, and therefore has excellent surface slipperiness and excellent resistance to UV-C light.
[0048] In the above first embodiment, silicone rubber is used as the material of the base material 111 in the second layer 11 of the laminated structure 1, but the same effect can be obtained by using a rubber component other than silicone rubber, such as chloroprene rubber, instead of silicone rubber. EXAMPLES
[0049] (Preparation of laminated structure 1) Four types of samples (specimens A1 to A4) were prepared to verify the UV-C light shielding effect of the second layer 11 of the laminated structure 1. First, 200 coaxial cables with a diameter of about 0.25 mm were twisted together and covered with a braided wire to prepare a cable core. Next, using an extruder, a sheath material was extruded around the outer periphery of the cable core at a speed of 5 m / min to form a sheath 23 with a thickness of 0.8 mm as the first layer 10 of the laminated structure 1 (cable outer diameter: about 8 mm). Here, the sheath material of the sample A1 was a commonly used PVC. Also, the sheath material of the samples A2 to A4 was a color batch containing titanium oxide (a mixture of "KE-color-W" and "KE-174-U" manufactured by Shin-Etsu Chemical Co., Ltd.). The Ti concentration was 0.12 mass % as analyzed by an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (SEM) (average value in a measurement area of 125 μm wide × 95 μm long). By the steps up to this point, samples A1 and A2 not having the coating 24 as the second layer 11 of the laminate structure 1 were produced.
[0050] Next, materials for forming the coating 24 of the sample A3 were prepared. An addition reaction type silicone rubber coating agent (product name: SILMARK-TM, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as a rubber component that would become the base material 111. In addition, silicone resin fine particles (product name: X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 5 μm were prepared as the first fine particles 112. 120 parts by mass of the silicone resin fine particles, 600 parts by mass of toluene as a solvent for adjusting viscosity, 8 parts by mass of a crosslinking agent (product name: CAT-TM, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.3 parts by mass of a curing catalyst (product name: CAT-PL-2, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed with 100 parts by mass of this rubber component to prepare a coating solution in which the ratio of the first fine particles 112 to the coating 24 was 55% by mass. The content of the first fine particles 112 in the coating 24 was calculated on the assumption that the coating agent hardens with almost no mass loss (almost equivalent to the blending mass ratio).
[0051] Next, the surface of the sheath 23 provided on the cable core was cleaned. After that, the cable core provided with the sheath 23 was immersed in the above coating solution by dip coating to form a coating film made of silicone rubber on the surface of the sheath. The coating film was then subjected to a sufficient drying and curing treatment at a temperature of 150°C to form a coating film 24 having an uneven surface. The coating film 24 of the obtained sample A3 had a film thickness of 15 μm. Through the above steps, sample A3 was produced.
[0052] Next, materials for forming the coating 24 of the sample A4 were prepared. For the coating 24 of the sample A4, in addition to the rubber component as the base material 111 and the silicone resin fine particles as the first fine particles 112, which are the same as those used for the coating 24 of the sample A3, titanium oxide (anatase type TiO2) fine particles having an average particle size of 250 nm were prepared as the second fine particles 113. Then, 120 parts by mass of the silicone resin fine particles, titanium oxide fine particles, 600 parts by mass of toluene as a solvent for adjusting viscosity, 8 parts by mass of a crosslinking agent (product name: CAT-TM, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.3 parts by mass of a curing catalyst (product name: CAT-PL-2, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed with respect to 100 parts by mass of the rubber component to prepare a coating solution in which the ratio of the first fine particles 112 to the coating 23 was 55% by mass, and the ratio of the second fine particles 113 to the coating 23 was a predetermined concentration. The concentration of the titanium oxide particles, which are the second particles 113, was adjusted so that the titanium concentration in the coating 24 (average value in a measurement area of 125 μm wide × 95 μm long) was 0.6 mass % as determined by an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (SEM). The content of the first particles 112 in the coating 24 was calculated on the assumption that the coating agent hardens with almost no mass loss (almost equivalent to the blending mass ratio).
[0053] Next, similarly to the coating 24 of sample A3, the surface of the sheath 23 was washed, a coating film was formed by dip coating, and the coating film was dried and cured to form a coating 24 having an uneven surface. The thickness of the coating 24 of the obtained sample A4 was 15 μm. Sample A4 was produced by the above steps.
[0054] (Verification of UV-C light blocking effect) In order to verify the UV-C light shielding effect of the second layer 11 of the laminated structure 1, tensile tests were carried out on the samples A1 to A4 before and after irradiation with UV-C light. First, the sheath 23 (sheath 23 covered with coating 24 in samples A3 and A4) of the cable-shaped samples A1 to A4 produced by the above method was cut along the length to remove the contents in the sheath 23 and open the sheath 23. Then, the opened sheath 23 was punched out with a No. 6 dumbbell to produce a dumbbell test piece (thickness 0.8 mm). Here, the dumbbell test pieces formed from the sheath 23 of samples A1, A2, A3, and A4 (sheath 23 covered with coating 24 in samples A3 and A4) are referred to as samples B1, B2, B3, and B4, respectively. The configurations of samples B1 to B4 are shown in Table 1 below.
[0055] [Table 1]
[0056] The tensile test was performed on the above samples B1 to B4 under the conditions of an environmental temperature of 15 to 35°C, an environmental humidity of 28 to 65 RH%, and atmospheric pressure, as specified in "JIS K6251 (1994)". UV-C light irradiation was performed using a storage cabinet with a germicidal lamp (Daishin Kogyo Co., Ltd. DM-5, Lamp GL-10) with an internal temperature of 25 to 40°C, an internal humidity of 28 to 65%, an internal pressure of 1 atm (atmospheric pressure), a wavelength of 253.7 nm, and an illuminance of 1.3 mW / cm. 2 The experiment was carried out under the condition of irradiation times of 100 and 200 hours. The illuminance meter used was the UVC-254A manufactured by MK Scientific.
[0057] FIG. 5(a) is a graph showing the results of the tensile test of sample B1. In FIG. 5(a), "unirradiated" indicates sample B1 in a state where it was not irradiated with UV-C light, and "after irradiation" indicates sample B1 after 200 hours of irradiation with UV-C light. As shown in FIG. 5(a), the strength (the magnitude of stress when the base breaks) and elongation are smaller after irradiation with UV-C light than before irradiation, and it was confirmed that sample B1 deteriorates (changes in properties such that it becomes more likely to break) due to irradiation with UV-C light. In addition, since sample B1 was a gray PVC, it was visually confirmed that a yellowish discoloration occurred due to irradiation with UV-C light. Note that 100% elongation means that the length of the dumbbell test piece became twice its original length.
[0058] FIG. 5(b) is a graph showing the results of the tensile test of sample B2. In FIG. 5(b), "unirradiated" indicates sample B2 in a state where it was not irradiated with UV-C light, and "after irradiation" indicates sample B2 after 200 hours of irradiation with UV-C light. As shown in FIG. 5(b), the strength and elongation after irradiation with UV-C light are smaller than those before irradiation, and it was confirmed that sample B2 deteriorates (changes) due to irradiation with UV-C light. In addition, no discoloration due to irradiation with UV-C light was visually confirmed for sample B2 (white) made of silicone rubber. On the other hand, compared with the graph in FIG. 5(a), it can be seen that the degree of deterioration due to irradiation with UV-C light is greater for silicone rubber than for PVC.
[0059] Although sample B2 contains TiO2 particles as second particles that absorb UV-C light, it is considered that the TiO2 particles have little effect on the resistance to UV-C light because of the low concentration (Ti concentration in sheath 23 is 0.12 mass%). Also, sample B2 does not have a coating corresponding to second layer 11, and therefore has inferior surface slipperiness compared to samples B3 and B4.
[0060] FIG. 6(a) is a graph showing the results of the tensile test of sample B3. In FIG. 6(a), "unirradiated" indicates sample B3 in a state where it was not irradiated with UV-C light, and "after irradiation" indicates sample B3 after 200 hours of irradiation with the above-mentioned UV-C light. As shown in FIG. 6(a), the strength and elongation were smaller after irradiation with UV-C light than before irradiation, and it was confirmed that sample B3 deteriorated due to irradiation with UV-C light. Moreover, as with sample B2, no discoloration due to irradiation with UV-C light was visually confirmed for sample B3 (white).
[0061] 6(a), cracks occurred in coating 23 corresponding to second layer 11 when elongation exceeded about 50%. Coating 23 of sample B3 contains silicone resin microparticles as first microparticles 112 that have excellent resistance to UV-C light, but it is believed that the silicone rubber in areas where these silicone resin microparticles are not present deteriorated, causing the cracks.
[0062] FIG. 6(b) is a graph showing the results of the tensile test of sample B4. In FIG. 6(b), "unirradiated" indicates sample B4 in a state where it was not irradiated with UV-C light, and "after irradiation" indicates sample B4 after 200 hours of irradiation with the above-mentioned UV-C light. As shown in FIG. 6(b), the strength and elongation are almost the same before and after irradiation with UV-C light, and it was confirmed that the deterioration of sample B4 due to irradiation with UV-C light was effectively suppressed. In addition, as with sample B2, no discoloration due to irradiation with UV-C light was visually confirmed for sample B4 (white).
[0063] Comparing the test results of sample B4 with those of sample B3, it can be seen that the titanium oxide microparticles as the second microparticles contained in the coating corresponding to the second layer 11 block UV-C light, thereby suppressing deterioration.
[0064] Fig. 7(a) is a graph showing the relationship between the UV-C light irradiation time and the stress at break of the substrate for samples B1 to B4, and Fig. 7(b) is a graph showing the relationship between the UV-C light irradiation time and the elongation at break of the substrate for samples B1 to B4.
[0065] 7(a) and (b), sample B3, which does not contain titanium oxide microparticles as the second microparticles in the coating corresponding to the second layer 11, shows a decrease in strength and elongation as the irradiation time of UV-C light increases. On the other hand, sample B4, which contains titanium oxide microparticles as the second microparticles in the coating corresponding to the second layer 11, shows no change in strength and elongation even when the irradiation time of UV-C light increases. Furthermore, sample B4 has a lower elongation before irradiation with UV-C light than sample B1, but a higher elongation after irradiation with UV-C light for 200 hours than sample B1. These results also show that the titanium oxide microparticles contained in the coating of sample B4 can suppress the progression of deterioration caused by UV-C light. EXAMPLES
[0066] A Raman mapping analysis was performed to investigate the distribution state of the second particles 113 in the second layer 11 of the laminated structure 1. The Raman mapping analysis is a method of performing Raman scattering measurement while scanning the surface of a sample with a laser, and mapping information obtained from the Raman scattering spectrum at each measurement point in two dimensions. The Raman mapping analysis was performed using the sample before irradiation with UV-C light.
[0067] The following Tables 2 and 3 show the measurement conditions and mapping conditions for the Raman scattering measurement, respectively. The Raman scattering measurement was performed using a RAMANforce Standard VIS-NIR-HS manufactured by Nanophoton Co., Ltd. The Raman scattering measurement was performed in an environment with an environmental temperature of 15 to 35°C, an environmental humidity of 25 to 65 RH%, and atmospheric pressure.
[0068] [Table 2]
[0069] [Table 3]
[0070] The mapping analysis according to this embodiment was carried out on the surface of four types of sheet-shaped silicone rubber films (specimens C1 to C4) as the second layer 11. Each of the specimens C1 to C4 includes silicone rubber as the base material 111, silicone resin fine particles having an average particle size of about 2 μm as the first fine particles 112, and titanium oxide fine particles mainly including anatase-type TiO2 fine particles having an average particle size of about 250 nm as the second fine particles 113. The content of the silicone resin fine particles in each of the specimens C1 to C4 is 60% by mass. The content of the silicone resin fine particles in each of the specimens C1 to C4 was calculated on the assumption that the silicone rubber coating agent hardens with almost no mass loss (almost equivalent to the blending mass ratio). Specifically, the mass of the silicone resin fine particles is divided by the total mass of the silicone resin fine particles, the titanium oxide fine particles, and the silicone rubber, and expressed as a percentage.
[0071] Table 4 below shows the silicone resin particles as the first microparticles 112 in samples C1 to C4, the silicone resin concentration in each sample, and the average particle size of the titanium oxide microparticles as the second microparticles 113 and the Ti concentration in each sample. The Ti concentration in the table was determined by SEM-EDS (average value in a measurement area of 125 μm wide x 95 μm long). Sample C1 corresponds to sample A4 (B4).
[0072] [Table 4]
[0073] Samples C1 to C4 differ in the blending amount of titanium oxide particles as the second particles 113. The Ti concentrations (evaluated by SEM-EDS) of samples C1, C2, C3, and C4 are 0.6 mass %, 1.1 mass %, 1.5 mass %, and 4.4 mass %, respectively.
[0074] FIG. 8 shows an example of a Raman scattering spectrum measured at a certain point on the sample C1. -1 Near (for example, 640±20cm-1 The peak at about 2915 cm (referred to as the first peak) is a particularly intense peak in the scattering spectrum of titanium oxide fine particles (mainly including anatase-type TiO fine particles), which is mainly derived from the lattice vibration Eg of anatase-type TiO. -1 Near (e.g., 2915±33cm -1 ) (referred to as the second peak) is a particularly intense peak in the scattering spectrum of silicone resin, which is due to the CH stretching of silicone resin. In the Raman mapping analysis according to this embodiment, the distribution of titanium oxide microparticles and silicone resin microparticles was mapped using the intensities of these first and second peaks. When the titanium oxide microparticles mainly contain rutile-type TiO2 microparticles, the first peak is approximately 445 cm, which is due to the lattice vibration Eg. -1 Near (for example, 445±45cm -1 In addition, when the titanium oxide fine particles mainly contain brookite-type TiO2 fine particles, it is preferable to use the peak at about 150 cm as the first peak. -1 Near (for example, 150±15cm -1 It is preferable to use the peak of
[0075] Figures 9(a), 10(a), 11(a), and 12(a) are mapping images of samples C1, C2, C3, and C4 obtained by mapping analysis, respectively. The size of these mapping images (mapping area) is 22.5 μm × 22.5 μm.
[0076] The mapping analysis was carried out using the analysis software Raman Viewer Ver.4.5.54 manufactured by Nanophoton Corporation. The shading of the titanium oxide fine particles in Fig. 9(a), Fig. 10(a), Fig. 11(a), and Fig. 12(a) was set within an intensity range of 20 to 3500 so that the shading becomes darker as the intensity of the first peak increases. Then, it was set that titanium oxide fine particles exist for values within a range of 1760 to 3500. The shading of the silicone resin fine particles in the silicone resin fine particles was set within an intensity range of 400 to 3000 so that the shading becomes darker as the intensity of the second peak increases. Then, it was set that silicone resin fine particles exist for values within a range of 1700 to 3000. The silicone rubber region, which is the base material 111, where neither the silicone resin fine particles nor the titanium oxide fine particles are observed, is observed in a different color from these regions.
[0077] 9(a), 10(a), 11(a), and 12(a), it can be seen that the titanium oxide microparticles segregate around the silicone resin microparticles and efficiently fill the areas where the silicone resin microparticles are not present (areas between the silicone resin particles). This is because the average particle size of the titanium oxide microparticles is smaller than the average particle size of the silicone resin microparticles (for example, 1 / 2 or less, more preferably 1 / 5 or less). Furthermore, as the amount of titanium oxide microparticles increases, the proportion of the area occupied by titanium oxide microparticles in the area where the silicone resin microparticles are not present increases, and when the Ti concentration is 1.5 mass% or more, almost all of the area where the silicone resin microparticles are not present (areas with low resistance to UV-C light) is occupied by titanium oxide microparticles.
[0078] That is, the second layer 11 has a region where the intensity of the first peak in the region where the silicone resin microparticles are present (region A that appears circular and white in Figures 9(a), 10(a), 11(a), and 12(a)) is smaller than the intensity of the first peak in the region where the silicone resin microparticles are not present (region B that is located between the silicone resin microparticles) because the titanium oxide microparticles are preferentially present in regions where the silicone resin microparticles are not present. Thus, in the second layer 11, the titanium oxide microparticles are not uniformly dispersed, and the titanium oxide microparticles segregate around the silicone resin microparticles.
[0079] Figures 9(b), 10(b), 11(b), and 12(b) are binarized analysis images obtained by binarizing the mapping images of Figures 9(a), 10(a), 11(a), and 12(a), respectively.
[0080] This binary analysis was performed using the "area ratio analysis" function of the above-mentioned analysis software Raman Viewer Ver. 4.5.54. In this binary analysis, the integration range of the first peak was 38.7 cm -1 The integral intensity of the first peak was applied to the calculation, and the integral range of the second peak was 35.2 cm -1 The integrated intensity of the second peak was applied to the calculation as the intensity of the second peak. In Raman Viewer Ver. 4.5.54, the intensity calculation method in the binarization analysis is called area calculation.
[0081] According to the binarized analysis images shown in Figures 9(b), 10(b), 11(b), and 12(b), the ratios of the area of titanium oxide microparticles to the area other than titanium oxide microparticles (i.e., the total area of silicone resin microparticles and silicone rubber) are 6.4 to 93.6, 12.8 to 87.2, 22.7 to 77.3, and 35.2 to 64.8, respectively.
[0082] From the above results, it was found that when the ratio of the area of titanium oxide microparticles to the total area of titanium oxide microparticles and silicone resin microparticles in the binarized analysis image performed under the above conditions is 22.7% or more, almost all of the area in the area where silicone resin microparticles are not present is occupied by titanium oxide microparticles, and the second layer 11 has excellent resistance to UV-C light. It is considered that the condition for the second layer 11 to have excellent resistance to UV-C light is satisfied even when the silicone resin microparticles as the first microparticles 112 are replaced with other microparticles such as silica microparticles, or when the titanium oxide microparticles as the second microparticles 113 are replaced with other microparticles such as carbon microparticles. It is noted that, from the viewpoint of reducing the static friction coefficient, a certain amount of area where silicone resin microparticles are present is necessary, so that the upper limit of the ratio of the area of titanium oxide microparticles to the total area of titanium oxide microparticles and silicone resin microparticles in the binarized analysis image is preferably 50% or less.
[0083] (Summary of the embodiment) Next, the technical ideas grasped from the above-described embodiment will be described by using the reference numerals and the like in the embodiment. However, the reference numerals and the like in the following description do not limit the components in the claims to the members and the like specifically shown in the embodiment.
[0084] [1] A laminated structure (1) comprising: a first layer (10) serving as a substrate; and a second layer (11) formed from a rubber composition including a rubber component (111), first microparticles (112) for imparting unevenness to a surface, and second microparticles (113) for blocking UV-C light, the second layer (11) being laminated on the first layer (10), wherein in a mapping image obtained by Raman mapping analysis of the first microparticles (112) and the second microparticles (113) using a first peak derived from vibration of the second microparticles (113) and a second peak derived from vibration of the first microparticles (112) contained in a Raman scattering spectrum obtained by Raman scattering measurement of the second layer (11), the second microparticles (113) are more present in an area where the first microparticles (112) are not present than in an area where the first microparticles (112) are present.
[0085] [2] The laminated structure (1) according to the above [1], wherein the rubber component (111) is silicone rubber, and the first microparticles (112) are made of a material containing Si that has higher resistance to UV-C light than the silicone rubber.
[0086] [3] The laminated structure (1) according to the above [1] or [2], wherein the first fine particles (112) are silicone resin fine particles and / or silica fine particles.
[0087] [4] The laminated structure (1) according to any one of the above [1] to [3], wherein the second fine particles (113) are titanium oxide fine particles.
[0088] [5] The laminate structure according to the above [4], wherein the second layer has a Ti concentration of 1.5 mass % or more.
[0089] [6] A cable (20) comprising an insulator made of the laminated structure (1) according to any one of the above [1] to [5].
[0090] [7] A tube (40a, 40b, 40c) provided with an insulator made of the laminated structure (1) according to any one of the above [1] to [5].
[0091] [8] A laminated structure (1) comprising: a first layer (10) having a silicone rubber base material; and a second layer (11) laminated on the first layer (10), the second layer (11) having a silicone rubber base material (111) and including first microparticles (112) for imparting unevenness to the surface and second microparticles (113) for absorbing UV-C light, wherein the first microparticles (112) are made of a material containing Si that is more resistant to UV-C light than the silicone rubber, and the second microparticles (113) have an average particle size that is half or less of the average particle size of the first microparticles (112).
[0092] Although the embodiment and examples of the present invention have been described above, the present invention is not limited to the above embodiment and examples, and various modifications can be made within the scope of the gist of the invention. Furthermore, the above-described embodiment and examples do not limit the invention according to the claims. Furthermore, it should be noted that not all of the combinations of features described in the embodiment and examples are essential to the means for solving the problems of the invention. [Explanation of symbols]
[0093] 1. Laminated structure 10 First Layer 111 Base material 112 The First Particle 113 Second Particle 11 Second Layer 2 Ultrasound Probe Cable 20 Cable 23 Sheath 24 Coating 40a, 40b, 40c Medical tubing 41 Tube body 42 Outer coating 43 Inner Capsule
Claims
1. A first layer serving as a substrate; a second layer formed from a rubber composition including a rubber component, first microparticles for imparting unevenness to a surface, and second microparticles for blocking UV-C light, the second layer being laminated on the first layer; A method for producing a laminated structure comprising: providing the first layer; applying a liquid rubber composition containing the first fine particles and the second fine particles onto the first layer to form a coating film; curing the coating to form the second layer; having A method for manufacturing a laminated structure.
2. The average particle size of the second fine particles is smaller than the average particle size of the first fine particles. A method for producing the laminated structure according to claim 1 .
3. The first fine particles have an average particle size of 1 μm or more and 10 μm or less, The average particle size of the second fine particles is 10 nm or more and 1 μm or less. A method for producing the laminated structure according to claim 2.
4. a first peak derived from vibration of the second fine particles and a second peak derived from vibration of the first fine particles included in a Raman scattering spectrum obtained by Raman scattering measurement of the second layer, the second fine particles are more present in an area where the first fine particles are not present than in an area where the first fine particles are present, A method for producing the laminated structure according to any one of claims 1 to 3.
5. the rubber component is a silicone rubber, the first microparticles are made of a material containing Si that has higher resistance to UV-C light than the silicone rubber; A method for producing the laminated structure according to any one of claims 1 to 4.
6. The first microparticles are silicone resin microparticles and / or silica microparticles. A method for producing the laminated structure according to any one of claims 1 to 5.
7. The second fine particles are titanium oxide fine particles. A method for producing the laminated structure according to any one of claims 1 to 6.
8. The Ti concentration of the second layer is 1.5 mass% or more. A method for producing the laminated structure according to claim 7.
9. An insulating material comprising the laminated structure according to any one of claims 1 to 8, How the cable is manufactured.
10. An insulating material comprising the laminated structure according to any one of claims 1 to 8, A method for manufacturing tubes.
Citation Information
Patent Citations
Reflective material
JP2011221518A
Ultraviolet shielding silicone coating composition and coated article
JP2012077267A
Cable and medical hollow tube
JP2020038824A
Cables and medical hollow tubes
JP6723489B1
Cable and medical hollow tube
US20190352848A1
